Educating Users to Generate Secure Graphical Password Secrets: An Initial Study - Fatehah, MD; Jali, MZ; Wafa, MK; Anuar, NB (IEEE, 2024)
The username/password combination is still the most widely used method albeit various user authentication techniques have been introduced. Numerous studies have been conducted to investigate the scheme and it could be summarized that despite it weaknesses, it is the most favourable scheme. Thus, to reduce the weakness, authenticating users with image or pictures (i.e. graphical password) is proposed as one possible alternative as it was claimed that pictures were easy to remember, easy to use and has considerable security. This paper presents a study carried out to investigate initial user's performance and feedback towards the use of hybrid graphical methods (i.e. combining two graphical methods) as a method of authentication. Initially, a survey was conducted to identify participants' drawing patterns as their secret using paper-based method, and then the graphical software prototype was developed and pilot tested by selected participants. Overall, the pilot test on the prototype showed positive results as participants enjoyed using it and able to register within tolerable time.